Load Influence Compensation in the Harmonious Program Controlled Two-dimensional Servo Systems - Gelezevicius, V.; Babkaitis, V. (Elektronika ir Elektrotechnika, 2000)
The method of the motor loading torque fixation at the moment when its shaft makes a move is presented. This fixed torque value is used for forming of the supplementary control signal applied for the loading torque influence to the positioning process quality compensation. The presented results of simulation show the efficiency of the proposed method in the program controlled positioning system case, when motion trajectory is programmed by the form of trapezium velocity diagrams. The method of harmonious program controlled two-dimensional servo system realisation using the loading torque influence compensation principle is presented.